The therapeutic agents that target ATP-sensitive potassium channels - Rubaiy Hussein N. (Acta Pharmaceutica, 2016)
ATP-sensitive potassium (KATP) channels are a major drug target for the treatment of type-2 diabetes. KATP channels are ubiquitously expressed and link the metabolic state to electrical excitability. In pancreatic β-cells, KATP channels are crucial in the regulation of glucose-induced insulin secretion. Also, KATP channels are involved in the protection against neuronal seizures and ischaemic stress in the heart, brain and in the regulation of vascular smooth muscle tone. Functional KATP channels are hetero-octamers composed of two subunits, a pore forming Kir6, which is a member of the inwardly rectifying potassium channels family, and a regulatory sulphonylurea receptor (SUR). In response to nucleotides and pharmaceutical agonists and antagonists, SUR allosterically regulates channel gating. The allosteric communication pathways between these two heterologus proteins in KATP channels are still poorly understood. This review will highlight the therapeutic agents that target KATP channels and are used to treat diabetes and cardiovascular diseases.